Presynaptic vesicular accumulation is required for antipsychotic efficacy in psychotic-like rats - Uzuneser, Taygun; Weiss, Eva Maria; Dahlmanns, Jana; Kalinichenko, Liubov; Amato, Davide; Kornhuber, Johannes; Alzheimer, Christian; Hellmann, Jan; Kaindl, Jonas; Hübner, Harald; Löber, Stefan; Gmeiner, Peter; et al. (Journal of Psychopharmacology, 2021)
Background: The therapeutic effects of antipsychotic drugs (APDs) are mainly attributed to their postsynaptic inhibitory functions on the dopamine D2 receptor, which, however, cannot explain the delayed onset of full therapeutic efficacy. It was previously shown that APDs accumulate in presynaptic vesicles during chronic treatment and are released like neurotransmitters in an activity-dependent manner triggering an auto-inhibitory feedback mechanism. Although closely mirroring therapeutic action onset, the functional consequence of the APD accumulation process remained unclear. Aims: Here we tested whether the accumulation of the APD haloperidol (HAL) is required for full therapeutic action in psychotic-like rats. Methods: We designed a HAL analog compound (HAL-F), which lacks the accumulation property of HAL, but retains its postsynaptic inhibitory action on dopamine D2 receptors. Results/outcomes: By perfusing LysoTracker fluorophore-stained cultured hippocampal neurons, we confirmed the accumulation of HAL and the non-accumulation of HAL-F. In an amphetamine hypersensitization psychosis-like model in rats, we found that subchronic intracerebroventricularly delivered HAL (0.1 mg/kg/day), but not HAL-F (0.3–1.5 mg/kg/day), attenuates psychotic-like behavior in rats. Conclusions/interpretation: These findings suggest the presynaptic accumulation of HAL may serve as an essential prerequisite for its full antipsychotic action and may explain the time course of APD action. Targeting accumulation properties of APDs may, thus, become a new strategy to improve APD action.
CRIS-Team Scopus Importer:2020-12-11
Keywords: behavior; Haloperidol; presynaptic accumulation; schizophrenia